Mathematical Reasong and Math Anxiety on Connected Mathematics Project Based on Quantum Learning (Unnes Journal of Mathematics Education Research, 2019)
This research aims were (1) to know the quality of Connected Mathematics Project based on Quantum Learning and (2) to describe the reasoning patern based on math anxiety category. This study was a mixed method research with using concurrent embedded design. The population was VII grader students of SMPN 2 Salam, Magelang regency. The subjects was selected based on math anxiety category, such as low, middle, and high level. Data was collecting by questionnaire, observation, test, and interview. The result showed that (1) Connected Mathematics Project based on Quantum Learning was on good category (2) Students with low level of math anxiety satisfied six indicators of mathematical reasoning, students with middle level of math anxiety satisfied three indicators of mathematical reasoning, and students with high level of math anxiety satisfied the two indicators of mathematical reasoning.